Preface - Hartman, Björn; Horvitz, Eric (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
The HCOMP conference was created as a venue for exchanging ideas and developments on principles, experiments, and implementations of systems that rely on programmatic access to human intellect to perform some aspect of computation, or where human perception, knowledge, reasoning, or coordinated physical activities contributes to the operation of larger systems and applications. Topics covered in the evolving discipline of human computation and crowdsourcing include efforts in human-computer interaction (HCI), computer-supported collaborative work (CSCW), cognitive psychology, organizational behavior, economics, information retrieval, databases, computer systems, optimization, and multiple areas of artificial intelligence (AI), such as vision, speech, robotics, machine learning, mechanism and market design, and planning. The links to AI are as strong as those to HCI, CSCW, and economics; human computation promises to play an important role in research on principles of artificial intelligence as well as in the engineering of systems that can take advantage of the (changing) complementarities of human and machine intellect.